The correlation between duration of illness and hemoglobin A1c levels with quality of life in children with type 1 diabetes mellitus - Garindra Wicaksono, - (2021)
Children with type 1 diabetes mellitus (T1DM) are in a chronic condition that requires daily care throughout life and interferes the quality of life. This research was an analytical observational study with a cross-sectional design at the Pediatric Endocrinology Outpatient Clinic in Dr. Soetomo General Hospital, Surabaya. The sample size of this study was 29 subjects. Data were accumulated through interviews, questionnaires, and medical records. To determine whether there is a relationship among the duration of illness, HbA1c levels, and the quality of life in children with T1DM, a correlation test with Pearson will be conducted. The Multiple Linear Regression test was carried out to determine how big the influence of the relationship. The results showed that from a total sample of 34 subjects, the average duration of illness was 21.24 (±14.82) months, the highest HbA1c level was 9 (6-13) %. The analysis results with the independent sample T-test were obtained with a value of p=0.877 (p <0.05), means that there was no notable difference between children and parents reports. The relationship among duration of illness, HbA1c, and quality of life were analyzed by Pearson Correlation test and Multiple Linear Regression test. The correlation results for length of illness and HbA1c sequentially r= 0.743, r= -0.857 with R2 value: 78.4% and p=0.001(p<0.05). From this study, it was also found that there was a positive relation between duration of illness and quality of life along with a negative correlation between HbA1c and quality of life.